Adams’ Theory of Nouthetic Counseling - Carter, John D. (Journal of psychology and theology, 1975)
Adams’ theory of nouthetic counseling was analyzed with reference to the nature of man, view of pathology, the counseling model, the counseling process, and the counselor and his techniques. Biblically, Adams’ theory is found to be inadequate. It views man almost entirely in behavioral terms and fails to incorporate such biblical concepts as heart, soul, spirit, and flesh. Adams also fails to provide a biblical basis for building his theory around the word noutheteo. Psychologically, Adams offers no emperical support for his theory and seems unaware of the methodological and research problems involved in supporting his claims of success. Adams’ criticism of Rogers and Freud shows a lack of knowledge of primary sources, and his uncritical positive bias toward Mowrer and Skinner reflects an uncritical presuppositionalism. Finally, he has no theory of motivation or theory of personality.